IN-VITRO ANTIOXIDANT ACTIVITY AND QUANTITATIVE ANALYSIS OF TOTAL PHENOLIC AND FLAVONOID COMPOUNDS OF Sebastiania chamaelea Muell. Arg. LEAF EXTRACTS - N. YASODAMMA; K.S. SHANTHI SREE; C. ALEKHYA; A.JOB ROGER BINNY (International Journal of Pharma and Bio Sciences, 2013)
The importance of antioxidant constituents in maintenance of health attracted research in plant based antioxidants. Presence of amino acid argenine and secondary metabolites like flavonoids and phenolic compounds and antibacterial activity leads for the evaluation of antioxidant activity of Sebastiania chamaelea leaf aqueous extracts. In-vitro free radical scavenging LC 50 at 100-90 µg/ml, and r educing ability EC50 at 175µg/ml are closely resembled to that of the standard drug ascorbic acid. The antioxidant activity also supported by the evaluation of the total phenolic compounds 235 µg/ml Gallic acid equivalent and flavonoids 210µg/ml as Quercetin Equivalent. S. chamaelea antioxidant activity may also support the herbal usage against vertigo, astringent, remedy for syphilis and diarrhoea.